Integrated Local Wisdom with 21st – Century Skills for Arabic-Speaking Material Model - Mohamad Sarip; Andri Ilham; Hendrawanto Hendrawanto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
The purpose of this study was to develop an integrated model of Arabic-speaking teaching materials with 21st-century skills and the value of local wisdom. This study used a mixed method approach, combining research and development techniques (R and D) using the Borg and Gall model. Participants were teachers (to do the peer assessment of the product / n = 3), experts (Arabic materials, curriculum / n = 2), and students (to get the needs analysis / n = 100). Data collection techniques include observations, questionnaires, tests, documents, and interviews. Data analysis uses qualitative and quantitative techniques. The results of this show that the model of teaching materials that have been developed is feasible to be applied in Arabic-speaking classes. The findings also show that the designed teaching materials have local wisdom values that can act as authentic materials. These teaching materials can not only build 21st-century skills but also build character education through the value of local wisdom. So, teaching materials that are integrated with the skills needs of the 21st century can facilitate learning objectives in producing quality graduates.